2021
DOI: 10.1002/jts.22753
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of the Posttraumatic Stress Disorder Checklist for DSM‐5 in a Canadian psychiatric outpatient sample

Abstract: The Posttraumatic Stress Disorder (PTSD) Checklist for DSM-5 (PCL-5) is a widely used, self-report measure that is employed to assess PTSD symptom severity and determine the presence of probable PTSD in various trauma-exposed populations. The PCL-5 is often administered in clinical settings as a screening tool for PTSD, with a suggested cutoff score of 33 indicating a probable PTSD diagnosis. Recent research indicates that a higher cutoff may be required in psychiatric samples. In the present study, we aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Our four-factor model aligns with the Posttraumatic Stress Disorder Checklist (PCL) (37) and the Mississippi Scale for Combat-Related PTSD (MCCP) (38), which similarly categorize PTSD into four dimensions (39). This correspondence, however, diverges from the PTSD Checklist for DSM-5 (PCL-5) (40) and the Impact of Event Scale-Revised (IES-R) (34), which include a fifth Iran J Psychiatry Behav Sci.…”
mentioning
confidence: 60%
“…Our four-factor model aligns with the Posttraumatic Stress Disorder Checklist (PCL) (37) and the Mississippi Scale for Combat-Related PTSD (MCCP) (38), which similarly categorize PTSD into four dimensions (39). This correspondence, however, diverges from the PTSD Checklist for DSM-5 (PCL-5) (40) and the Impact of Event Scale-Revised (IES-R) (34), which include a fifth Iran J Psychiatry Behav Sci.…”
mentioning
confidence: 60%
“…For the Chinese version of the PCL-5, a cutoff point of 37 was the one that had the best predictive values (Youden index J = 0.979). According to previous studies, the cutoff scores of PCL-5 was suggested ranging from 25 to 45 [5,6,[61][62][63][64] in different populations. Our indicated value of 37 was average compared to these studies.…”
Section: Discussionmentioning
confidence: 99%